2012
DOI: 10.1097/scs.0b013e31824f66a0
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes Comparing 2% Lidocaine and 4% Articaine With Epinephrine 1

Abstract: The hemodynamic parameters evaluated in third molar surgery with 2% lidocaine and 4% articaine (both with epinephrine 1:100,000) did not show significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
2
19
2
1
Order By: Relevance
“…Despite the fact that the authors used only four time points during the procedure, the results were the same as those recorded in the present study, which used seven distinct time points, similar to a previous study (Santos et al). However, the same study (de Morais et al, 2012a) did not confirm the presence of alterations between the time points within each group, unlike the present study. These assessments confirmed significant variations within each group for certain hemodynamic variables during the procedure.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Despite the fact that the authors used only four time points during the procedure, the results were the same as those recorded in the present study, which used seven distinct time points, similar to a previous study (Santos et al). However, the same study (de Morais et al, 2012a) did not confirm the presence of alterations between the time points within each group, unlike the present study. These assessments confirmed significant variations within each group for certain hemodynamic variables during the procedure.…”
Section: Discussioncontrasting
confidence: 55%
“…The surgical technique and the surgeon should be the same for all procedures, and the patients should be carefully selected to ensure similar trauma during both surgical operations (Lökken et al, 1975). It is also important to highlight that the results of the present study were obtained with identical volumes of both of the anesthetic solutions used (5.4 ml), thereby minimizing any bias, as was the case in earlier studies (Colombini et al, 2006;Santos et al, 2007;Vasconcellos et al;de Morais et al, 2012a). Even with the quantity of anesthetic limited to 5.4 ml, none of the patients complained of trans-operative pain during the surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, both 1:100,000 and 1:200,000 concentrations have shown to be safe in the volume used, thus in line with mentioned authors. In addition, Cáceres et al 19 have concluded that local anesthetic effect, with or without vasoconstrictor, has not induced significant cardiovascular parameters change, and Morais et al 2 and Bispo et al 20 have also concluded that different epinephrine concentrations associated to lidocaine and articaine have not changed cardiovascular parameters of volunteers. Similar to literature results, our study has shown that vasconstrictors in concentrations of 1:100,000 or 1:200,000 have not changed cardiovascular parameters and oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors such as inadequate choice of anesthetic solution, anesthetic salt overdose, accidental vasoconstrictor intravascular injection and fast administration of the solution may lead to increased blood concentration of the drug and to a higher potential for toxic effects 1,2 . Systemic complications of intravascular injection of local an-esthetics are basically induced by the interaction of adrenergic vasoconstrictors and sympathetic autonomous nervous system receptors, because its vasoconstrictor therapeutic action occurs by means of binding to α1 receptors.…”
Section: Introductionmentioning
confidence: 99%